Efektivitas Mediasi Dan Arbitrase Dalam Penyelesaian Sengketa Konsumen Kesehatan - Yuyut Prayuti; Arman Lany; Davin Takaryanto; Angkasa Ramatuan Hamdan; Beni Ciptawan; Enggar Adi Nugroho (Syntax Idea)
Settlement of health consumer disputes is an important issue in the health system because it is directly related to consumer rights and the quality of health services. Mediation and arbitration are two alternative dispute resolution methods that can be used in cases like this. The aim of this research is to analyze the effectiveness of mediation and arbitration in resolving health consumer disputes. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that mediation is considered effective in resolving health consumer disputes, while the effectiveness of arbitration depends on the expertise of the arbitrators, especially in cases that require special technical knowledge. Mediation tends to be more effective and efficient in resolving disputes because it can help disputing parties to reach an agreement voluntarily with the help of a mediator. However, mediation results are not final and usually require agreement from both parties to be binding. On the other hand, arbitration offers higher legal certainty because the decision is final and binding. However, the arbitration process tends to be more formal, time consuming, and more expensive than mediation. Therefore, the choice between mediation and arbitration must consider the needs and preferences of each party to the dispute.